Reação estromal e proteoglicanos de baixo peso molecular ricos em leucina - Coulson-Thomas, Vivien Jane [UNIFESP] (2010)
During cancer cell growth many tumors exhibit various grades of desmoplasia, unorganized production of fibrous or connective tissue, composed mainly of collagen fibers and myofibroblasts. The accumulation of extracellular matrix (ECM) surrounding tumors directly affects cancer cell proliferation, migration and spread, therefore the study of desmoplasia is of vital importance. Myofibroblasts synthesize an amalgam of products including collagens and other ECM proteins, such as proteoglycans and are activated during a desmoplastic reaction. Small leucine rich proteoglycans have been characterized surrounding breast and pancreatic tumors and have the ability to suppress cell proliferation. In this study we have analyzed desmoplasia co-cultivating colorectal cancer cells (Caco-2 and HCT116) and myofibroblasts using various co-culture systems. Our findings demonstrate that direct cell-cell contact between myofibroblasts and colorectal cancer cells evokes an upregulation of the expression of ECM components (collagen I, collagen III, collagen IV, collagen V, biglycan and fibromodulin) by myofibroblasts. The ECM accumulation produced when myofibroblasts are co-cultivated with colorectal cancer cells appears unorganized and in bundles. This ECM accumulation slowed the migration and invasion of the colorectal tumor cells in both monolayer and 3-D co-culture systems. The participation of the ECM components analyzed in this study in desmoplasia is also demonstrated in vivo in human colorectal carcinoma tissue, validating our in vitro system.